UM ESTUDO DAS INTERAÇÕES DOS JOVENS EM ESPAÇOS VIRTUAIS (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
We sought to reflect on the processes of interaction mediated by technologies with the following questions as a guide in the course: what does the interaction mediated by digital technologies consist of? What are the distinguishing elements of interaction in virtual spaces? Using netnography with participant observation as a research design, a study was carried out on the posts and interactions of young people on the social network Instagram. As a result, it was noticed that interactions are always a dialectical relationship between the social and the individual. In addition, the extraverbal horizon is essential for the success of interactions. Therefore, one must seek to understand how much this impacts on education actions that pervades the interaction mediated by technologies.
Keywords: Interaction; ICT; Social Media; Communication